Matriks dan Pengukuran Terhadap Kinerja Tata Kelola Teknologi Informasi - Maniah - (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
IT Governance is a function organizations run by leaders, top management and IT management who jointly monitor the implementation of IT strategies to ensure harmony between businesses and IT [1]. This paper will answer the question - "How to find out the settings and performance of IT governance in an organization?”. To answer, it can be done by setting the IT governance matrix and measuring the performance of IT governance applied to an organization. This research was conducted by way of case studies on an organization and using the template IT Governance one page and Assess your IT governance Performance [2]. The purpose of this study was to obtain an overview of the IT governance matrix and the value of IT governance performance at the Indonesian Post Company. The results of this study indicate that the arrangement of the IT governance matrix at Indonesian Post is Hybrid, which explains that IT Principle, IT Architecture, IT Infrastructure and IT are more spread to various divisions. Then the results of the performance evaluation of TI Indonesian Post governance show that the position is below average with a performance value of 65.6 (range 20 - 90, with an average value of 69) [2]. The contribution of the results of this study is to assist management in making decisions related to the sustainability of IT governance in the Indonesian Post Company.